2014
DOI: 10.1016/j.mmcr.2014.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system cryptococcoma in a Ugandan patient with Human Immunodeficiency Virus

Abstract: Mortality due to AIDS-related Cryptococcal meningitis (CM) is often >50% in low-middle income countries. Dissemination of CM can result in intracranial mass lesions known as cryptococcoma. Patients who develop cryptococcomas often have worse outcomes when compared to patients with cryptococcosis without cryptococcoma. We describe a cryptococcoma in the central nervous system (CNS) in a Ugandan patient with AIDS, and review the diagnosis and management with special focus on difficulties encountered in low or mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
(19 reference statements)
0
8
0
Order By: Relevance
“…Cryptococcoma may be indicated by the presence of a ring-shaped enhancement of mass lesions, with or without cystic changes, under MRI. The most common locations include the basal ganglia, cerebellum or parietal lobe, with the lesions being found more rarely in the intraspinal area and pons [ 27 , 28 ]. Most symptoms are similar to cryptococcal meningitis: headaches, nausea, vomiting, confusion and high body temperature, convulsions, depression, mental changes, drowsiness, confusion, polyuria, and cranial nerve tract deficiency [ 27 , 28 ].…”
Section: Etiological Factors Of Fis-cnsmentioning
confidence: 99%
“…Cryptococcoma may be indicated by the presence of a ring-shaped enhancement of mass lesions, with or without cystic changes, under MRI. The most common locations include the basal ganglia, cerebellum or parietal lobe, with the lesions being found more rarely in the intraspinal area and pons [ 27 , 28 ]. Most symptoms are similar to cryptococcal meningitis: headaches, nausea, vomiting, confusion and high body temperature, convulsions, depression, mental changes, drowsiness, confusion, polyuria, and cranial nerve tract deficiency [ 27 , 28 ].…”
Section: Etiological Factors Of Fis-cnsmentioning
confidence: 99%
“…Typically, the formation of cryptococcoma depends on an inflammatory response and are therefore more often seen in immunocompetent individuals or those who have initiated on ART. Case reports of cryptococcoma have described patients who presented with persistent neurological findings with sterile CSF or a low fungal burden [ 6 ]. This is because the walled off mass is thought to continuously shed Cryptococcus neoformans into the CSF [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Case reports of cryptococcoma have described patients who presented with persistent neurological findings with sterile CSF or a low fungal burden [ 6 ]. This is because the walled off mass is thought to continuously shed Cryptococcus neoformans into the CSF [ 6 ]. As with CM, the mainstay of treatment is combination amphotericin-based antifungal agents.…”
Section: Discussionmentioning
confidence: 99%
“…During our literature review we found only seven Englishlanguage case reports of cerebellar cryptococcoma caused by C. gattii (Li et al, 2010;Colom et al 2005;Velamakanni et al, 2014). Among them, three cases were treated with only antifungal drugs and four received surgical intervention along with antifungal treatment.…”
Section: Discussionmentioning
confidence: 99%